2002
DOI: 10.1080/08897070209511479
|View full text |Cite
|
Sign up to set email alerts
|

Use of Alcohol, Illicit Drugs, and Tobacco among Characters on Prime–Time Television

Abstract: Previous research of addictive substances suggests that use of alcohol, illicit drugs, and tobacco is overrepresented on prime-time television (TV). These studies, however, have relied on frequency counts of the substance, rather than the prevalence of use among characters. Therefore, the objectives of this study were to compare the prevalence of alcohol, illicit drug, and tobacco users among characters on prime-time TV during 1995 and 1996 with rates of use in the United States. In addition, we determined if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Youth aged 8-18 years are exposed to 8 hours and 33 minutes of media content daily [7], including content offering a substantial number of positive impressions of cigarette smoking [8][9][10]. Studies have demonstrated an association between exposure to certain media messages and smoking in adolescents.…”
mentioning
confidence: 99%
“…Youth aged 8-18 years are exposed to 8 hours and 33 minutes of media content daily [7], including content offering a substantial number of positive impressions of cigarette smoking [8][9][10]. Studies have demonstrated an association between exposure to certain media messages and smoking in adolescents.…”
mentioning
confidence: 99%
“…One detailed content analysis of MTV's reality show The Osbournes indicated that TV could deliver numerous messages related to the use of alcohol, tobacco, and other drugs, with more depictions implying endorsement than rejection of use (Blair et al 2005). There has been some systematic analysis of tobacco imagery on television including the US suggesting about one "smoking act" per hour of programming (Christenson, Henriksen & Roberts 2000) and about 2.5 % of TV prime time characters smoking (Long et al 2002), while Japanese research indicates four smoking acts per hour and virtually no negative portrayals of smoking (Kanda et al 2006;Sone 1999), and about two scenes in New Zealand's TV containing such imagery for every hour of programming (McGee & Ketchel 2006). To our knowledge there has been no published study of tobacco imagery on German TV.…”
mentioning
confidence: 99%
“…Our content analysis underlines the importance of more in-depth investigations of the way alcohol is portrayed on television. Many earlier studies have focused primarily on the intensity of alcohol portrayal in television programmes (Furnham et al, 1997;Long et al, 2002;Mathios et al, 1998;Wallack et al, 1990), implicitly assuming a positive relationship between exposure and attitudes or behaviours. In addition to the amount of alcohol consumption portrayed, it seems important to investigate the "lessons" adolescents may learn from the specific ways in which alcohol is portrayed.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the available studies into alcohol portrayal in the media focused only on the prevalence of alcohol consumption (Everett et al, 1998;Furnham et al, 1997;Gruber et al, 2005;Long et al, 2002;Mathios et al, 1998;Thompson & Yokota, 2001;Wallack et al, 1990) without systematically addressing the hedonic and social contexts in which it occurs. Like two earlier studies (Christenson, Henriksen, & Roberts, 2000;Hansen, 2003), we tried to extend the existing research by examining the specific contexts of alcohol use.…”
Section: Study 1: Alcohol Portrayal In the Soap Seriesmentioning
confidence: 99%
See 1 more Smart Citation